การตัดสินใจเลือกผู้จัดจำหน่ายเคมีภัณฑ์สิ่งทอ จากประเทศแถบเอเชีย โดยกระบวนการวิเคราะห์เชิงลำดับชั้น: กรณีศึกษา บริษัท วีวี จำกัด - ริ้วพิทักษ์, วรรัตน์ (Connexion: Journal of Humanities and Social Sciences, 2013)
The Objectives of this study were to find out the most important factor and the best Asian suppliers for textile chemical products. VV Co., Ltd., an import chemicals company, was used as our case study. As the import chemicals company, there were a lot of suppliers with different factors which could affect the company profit-for examples prices, taxes, quality of goods, etc. In this study “Analysis Hierarchy Process (AHP)” was used as analytical method to solve the problem: specifying, the most important factor in order to make the right decision of choosing the best supplier. Five factors, price, quality, responsibility, reliability and taxes, of suppliers were considered in our analytical method. Five different suppliers’ countries, China, Taiwan, Korea, India and Indonesia, were used as choices. As the result, it was found that the most important factor to select the most effective supplier was “prices” (31.8%) and of all the countries this study concludes that Korean (65%) suppliers as the most suitable.